Juridical Analysis of The Crime of Sexual Abuse of Early Childhood in Banyumas - Nazla Husnayain (UM Purwokerto Press, 2023)
This article wants to answer how legal certainty in the implementation of legal protection against children as victims of sexual abuse in Banyumas City, this research found that sexual crimes against early childhood committed in Banyumas Regency are very rampant.The act of sexual abuse can cause severe physical and psychological harm to the victim, especially if the victim is a young child who lacks the ability to protect herself, and is completely dependent on her caregivers and surroundings.The problem is whether the victim protection regulations are appropriate in juvenile criminal justice and how to prove and apply the law to minors, One of the institutions responsible for this is the Institute for the Protection of Women and Children (LPPA) in Banyumas Regency, The method of analyzing the juridical approach used by LPPA in handling cases of sexual abuse of early childhood in Banyumas Regency, The method used is normative juridical research with a statutory approach (statue approach).The data used is sourced from relevant laws, regulations and legislation.